Sosialisasi Manfaat Qris Pada Era Digital Di Desa Tanjung Selamat - Vivi Silvia; Audy Gesta Delila; Fifi Zhafirah; Septi Widya Sari (CV. ITTC INDONESIA, 2024)
This research aims to determine the interest of the Tanjung Selamat Village community in the existence of the Quick Response Code Indonesian Standard (QRIS) in the current digital era. By knowing the benefits of Qris, it is hoped that people will be able to use Qris more in the MSME and non-MSME sectors. The main activity of socializing Qris in Tanjung Selamat Village is to encourage MSMEs to use Qris in this increasingly sophisticated digital era, as well as to make transactions between traders and buyers easier.